IMPLEMENTASI PEMBELAJARAN SAINS BERBASIS ALAM DI SMP SEKOLAH ALAM CIKEAS-BOGOR - Ari Hakiki; Suci Siti Lathifah; Triasianingrum A (Jurnal Visi Ilmu Pendidikan)
This research is a qualitative reseach with descriptive analytic method. The purpose of this study was to describe an analyze science learning at Cikeas-Bogor School Of  Nature Midlle School. This research was carried out from January 2019 to Juny 2019 with several informants namely Science Teacher, Principal, Head Of Education Division, Head Of Research and Development, Head Of General Division, Vice Chancellor For Curriculum, Vice Chancellor For Student Affairs and Learners. This research was conducted with direct contact with the subject of research foun in the field and obtained two types of data, namely primary data derived  from interviews and observations, as well as secondary data derived from study documentation, based on data analysis, science learning based nature is divided into 3 processes, namely planning, implementation and evaluation. Learning planning uses thematic integrative. This competency refers to 5 basic concepts of  Nature Cikeas School of nature, namely morality, leadership, scientific logic, entrepreneurship and nationality. Continued by making spider web and outlining it into learning activities with scientific approaches. Learning method with nature, as well as learning resources through book and internet. The implementation of learning consists of school learning, RLE (Relife Education) and PBL (Project Based Learning) carried out in a relaxed and fun way, done in nature, and parents of students play an active role in the implementation of learning. Learning evaluation consists of the  percentage of results of RLE (Relife Education), test in the form of descriptions, PBL (Project Based Learning) and RPD (Raport Self Potential). Learning with nature is a learning method that is applied in science learning to teach students to build logical thinking.